1982
DOI: 10.2165/00003088-198207040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Cerebrospinal Fluid

Abstract: The distribution of drugs into the cerebrospinal fluid has long been considered a challenging field of investigation in 2 major respects: (a) understanding how the physicochemical properties (molecular weight, pKa, plasma protein binding) of various molecules influence their movements across such a specific structure as the blood-brain barrier; and (b) defining the relationship between cerebrospinal fluid concentrations of various drugs and their central (side) effects. An attempt has been made to review the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 149 publications
3
46
0
Order By: Relevance
“…The AUCCSF/AUCtotal plasma ratios were 0.009 and 0.015 for the (R)-and the (S)-forms, respectively. In view of the low protein content of the CSF, drugs are usually assumed to be largely in the unbound form in this compartment [7]. Subsequently, the CSF concentrations were compared with the corresponding unbound plasma concentrations ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUCCSF/AUCtotal plasma ratios were 0.009 and 0.015 for the (R)-and the (S)-forms, respectively. In view of the low protein content of the CSF, drugs are usually assumed to be largely in the unbound form in this compartment [7]. Subsequently, the CSF concentrations were compared with the corresponding unbound plasma concentrations ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The CSF white blood cell counts were normal. Thus, the blood-brain barrier may be considered as virtually undamaged [7].…”
Section: Methodsmentioning
confidence: 99%
“…CSF drug concentrations have been used as a common surrogate for unbound brain concentrations in clinical studies (Bonati et al, 1982;Cherubin et al, 1989;Garver, 1989;Reiter and Doron, 1996;Ostermann et al, 2004). Nevertheless, the reliability of using CSF drug concentration as a substitute has been challenged as the transport direction is different between the BBB and BCSFB for the two main efflux drug transporters, P-gp and BCRP (Bonati et al, 1982;Rao et al, 1999;de Lange and Danhof, 2002;Kusuhara and Sugiyama, 2004;Zhuang et al, 2006;de Lange, 2013;Kalvass et al, 2013). Furthermore, Gazzin et al (2008) reported that choroid plexus-associated P-gp content was less than 0.5% of the level in the cerebral microvessels, indicating that P-gp efflux is not important at the BCSFB.…”
Section: Introductionmentioning
confidence: 99%
“…The passage of drugs into cerebrospinal fluid depends on many factors, including pKa, protein binding and the state of the blood-brain barrier [1]. Since ,-lactam antibiotics are weak organic acids, they penetrate the cerebrospinal fluid poorly under normal conditions [2].…”
Section: Introductionmentioning
confidence: 99%